Exploring the Online and Blended Modes of Learning for Post-COVID-19: A Study of Higher Education Institutions - Lavina Sharma; Sonal Shree (MDPI AG, 2023)
The advent of the COVID-19 pandemic brought a tectonic shift in the otherwise traditional education sector. The classroom teaching approach, which has been followed in educational institutions for a long time, suddenly shifted to include e-learning through virtual platforms. Technological savviness is no longer a choice. As institutions were contemplating opening their campuses to students, they faced a dilemma to include a mode of learning that could impact the students positively and increase their overall learning effectiveness. At the same time, a total online mode of learning was not inclusive enough for the learners without access to seamless internet connectivity. In this context, the present study aims to draw a comparison between the three modes of learning: face-to-face education, online learning, and blended learning. The difference in the three modes of learning was assessed on the content of the course, facilitation, perceived value, and learning effectiveness. The data for the study were collected from 119 students studying in Higher Education Institutions (HEIs). The study's findings suggest a significant difference between the three modes of learning in terms of facilitation, perceived value, and learning effectiveness. However, the results also suggest that there was no significant difference between the three modes in terms of content. While content creates a more substantial impact through some parameters in one particular mode of learning, it does not create a similar impact through others. The study also delves into a pairwise comparison of each construct's learning modes that have shown a significant difference. The results can guide institutions towards choosing a suitable mode of learning for the students by considering a holistic approach.